The Digital Transformation of SMEs - (:unkn) unknown (OECD, 2021)
Despite potentially tremendous benefits, small and medium-sized enterprises (SMEs) lag in the digital transformation. Emerging technologies, as diverse as they are, offer a range of applications for them to improve performance and overcome the size-related limitations they face in doing business. However, SMEs must be better prepared, and stakes are high. SMEs make the most of the industrial fabric in many countries and regions, they create jobs (most jobs sometimes) and are the cement of inclusive and sustainable societies. The SME digital gap has increased inequalities among people, places and firms, and there are concerns that the benefits of the digital transformation could accrue to early adopters, further broadening these inequalities. Enabling SME digitalisation has become a top policy priority in OECD countries and beyond. The report looks at recent trends in SME digital uptake, including in the context of the COVID-19 crisis. It focuses on issues related to digital security, online platforms, blockchain ecosystems, and artificial intelligence. The report identifies opportunities, risks of not going digital, and barriers to adoption. It looks to concrete policy action taken worldwide to speed the SME transformation and raises a series of considerations to advance the SME digital policy agenda. (Publisher, BIBB-Doku)
Keywords: S 3.2.1 KMU, Klein- und Mittlere Unternehmen; G 2.2.1 Technologisierung; Klein- und Mittelbetrieb; Digitalisierung; Transformation; Künstliche Intelligenz; OECD